Detection of Fe and Ti on the dayside of the ultrahot Jupiter MASCARA-1b with CARMENES - Guo, Boyue; Yan, F.; Nortmann, L.; Cont, D.; Reiners, A.; Pallé, E.; Shulyak, D.; Molaverdikhani, Karan; Henning, Thomas; Chen, G.; Stangret, M.; Czesla, S.; et al. (Astronomy and astrophysics, 2024)
Ultrahot Jupiters are a type of gaseous exoplanet that orbit extremely close to their host star, resulting in significantly high equilibrium temperatures. In recent years, high-resolution emission spectroscopy has been broadly employed in observing the atmospheres of ultrahot Jupiters. We used the CARMENES spectrograph to observe the high-resolution spectra of the dayside hemisphere of MASCARA-1b in both visible and near-infrared. Through cross-correlation analysis, we detected signals of Fe I and Ti I. Based on these detections, we conducted an atmospheric retrieval and discovered the presence of a strong inversion layer in the planet’s atmosphere. The retrieved Ti and Fe abundances are broadly consistent with solar abundances. In particular, we obtained a relative abundance of [Ti/Fe] as −1.0 ± 0.8 under the free retrieval and −0.4−0.8+0.5 under the chemical equilibrium retrieval, suggesting the absence of significant titanium depletion on this planet. Furthermore, we considered the influence of planetary rotation on spectral line profiles. The resulting equatorial rotation speed was determined to be 4.4−2.0+1.6 km s−1, which agrees with the rotation speed induced by tidal locking.
Online veröffentlicht: 2. Juli 2024
Gesehen am 13.10.2025